Physical characteristics of boulders formed in the tropically weathered granite - Md Dan, Mohd Firdaus; Muhamad, Edy Tonnizam; Komoo, Ibrahim; Alel, Mohd Nur Asmawisham (Penerbit UTM Press, 2015)
Deep weathering profile is a common phenomenon for humid tropic especially in Malaysia. The reactions of deep weathering under soil surface are decomposition of the massive rock and formation of thick stratum of soil and boulders. However, the occurrence of embedded boulders or loose blocks in the highly to completely weathered in the hilly area is not fully understood and investigated. This paper investigates the occurrence and physical characteristics of boulders in the granitic area. The parameters investigated are boulder’s discoloration, size, shape, rindlet properties and their distribution. Colour and shape were determined based on rock colour chart by Krumbein and Croft’s chart respectively. Size, rindlet and its distribution were determined based on field observation. Field results revealed that boulders in the hilly area can be found as shallow as 2 m from ground surface. In addition, it is found that boulder that embedded in deeper zone became larger in size and surrounded by thicker rindlet of up to 50 cm thick. Boulders embedded in soil stratum at weathering zone 4 and 5 are mostly independent and scattered around the weathering profile. The boulders can also be presented in various shapes; the smaller boulder is located at the upper zone more to flat to very spherical shape and rounded to well rounded edges, while the larger boulder that is located at lower zone more to sub-spherical shape and well rounded edges.